CHILDREN IN CONFLICT WITH THE LAW WITHIN THE ONLINE MEDIA FRAME - Ilahi, Hani Noor (Jurnal InterAct, 2018)
In a variety of mass communication literature, such as McQuail, Baran and Davis, or John Vivian the topic of media and its role toward children is always being discussed. However, although it plays a strategic role in the lives of children, not all media institutions have a child-friendly orientation. These can be seen, one of them through the news of children in conflict with the law that lately often reported, along with a significant increase in numbers from year to year. Although on the one hand the news has a positive impact as a means of public advocacy for victims' families, but on the other hand, media coverage, especially the online mass media, has the potential to form a negative stigma against children in conflict with the law with its tendentious language and trial (trial by the press). Using the Critical Discourse Analysis model of Norman Fairclough, this study reveals how children in conflict with the law are still discriminated through coverage that ignores the best interests of the child. Although there is a policy that regulates the issue of children in conflict with the law, but the in the reality, there is no law enforcement over the mistakes mad by the media. The patriarchal ideology that still exists in society and the lack of journalist sensitivity to child-friendl coverage is some of the reasons behind the ignorance.